Pengelolaan Zakat Produktif sebagai Instrumen Peningkatan Kesejahteraan Umat - Fitri, Maltuf (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2017)
The purpose of zakat management formally is to (1) improve the effectiveness and efficiency of services in the management of zakat, and (2) to increase the benefits of zakat to realize the welfare of society and poverty reduction. In this context, the distribution of zakat funds in addition to the consumptive purpose, can also be justified for the purpose of growing productive economic activities for mustahiq. By law, the use of zakat for productive economic activity is also not prohibited, as long as the mandatory of fulfilling the basic needs of mustahiq has been done. The use of zakat funds for productive economic activities is a conception to liberate the socio-economic life of mustahiq with a view to changing from the recipient of zakat to the payer of zakat. The implementation scheme of this concept is to build or grow a business unit in mustahiq through grant funding for business capital. Within a certain production cycle, mustahiq will also receive technical assistance and guidance from the zakat management institution in order to plan the establishment of a successful business unit and that mustahiq has a permanent source of income.Tujuan pengelolaan zakat secara formal adalah untuk meningkatkan efektifitas dan efisiensi pelayanan dalam pengelolaan zakat, dan meningkatkan manfaat zakat untuk mewujudkan kesejahteraan masyarakat dan penanggulangan kemiskinan. Dalam konteks ini, pendistribusian dana zakat selain untuk pemberian bantuan yang bersifat konsumtif, juga dapat dibenarkan untuk tujuan menumbuhkan kegiatan ekonomi produktif bagi penerima zakat (mustahik). Secara hukum, penggunaan zakat untuk kegiatan ekonomi produktif juga tidak dilarang, selama keberadaan para mustahik yang wajib dan harus dibantu sudah terpenuhi kebutuhan dasarnya. Penggunaan dana zakat untuk kegiatan ekonomi produktif adalah sebuah konsepsi untuk memandirikan penerima zakat secara sosial ekonomi dengan maksud untuk merubah dari penerima zakat menjadi pembayar zakat. Skema pelaksanaan dari konsep ini adalah membangun atau menumbuhkan unit usaha pada diri penerima zakat melalui pemberian dana hibah untuk modal usaha. Dalam satu siklus produksi tertentu, penerima zakat juga akan mendapat pendampingan dan bimbingan teknis dari lembaga pengelola zakat agar rencana membentuk unit usaha berhasil dan penerima zakat memiliki sumber pendapatan yang permanen.Â